Problems and pitfalls of retrospective survey questions in COVID-19 studies - Lena Hipp; Mareike Bünning; Stefan Munnes; Armin Sauermann (Survey Research Methods, 2020)
This paper examines and discusses the biases and pitfalls of retrospective survey questions that are currently being used in many medical, epidemiological, and sociological studies on the COVID-19 pandemic. By analyzing the consistency of answers to retrospective questions provided by respondents who participated in the first two waves of a survey on the social consequences of the COVID-19 pandemic, we illustrate the insights generated by a large body of survey research on the use of retrospective questions and recall accuracy.
Keywords: 330; retrospective questions; recall accuracy; COVID-19